DELIR DAN SEKSUALITAS INFANTIL DALAM “AL-FIRÂSH AL-SHAGHÎR” KARYA YEHIA HAKKI - As. Rakhmad Idris (Kantor Bahasa Lampung, 2017)
AbstractLiterary works are born from the social womb of society. Authors are just painters of everydayphenomena and human behaviors. The story of Yehia Hakki's